The power of nature : archaeology and human-environmental dynamics - Smith, Monica L., 1954- (University Press of Colorado, 2022)
"The Power of Nature address the force and impact of nature relative to human knowledge, action, and volition. Complex case studies address the ways in which nature retains the upper hand in human agentive environmental discourse, providing a new discussion of the role of human effects on the environment"--